Penser la fraternité - Săplăcan, Călin (Warszawskie Studia Teologiczne, 2019)
How can we think of a polysemous reality like that of brotherhood? We propose the theological paradigm of the frontier as a method. This paradigm will allow us: first, to read the forms of fraternity (in an articulation of the singular, the particular and the universal); second, to question fraternity anthropologically (which articulates the questions of origin, becoming and end); finally, to consider fraternity ethically (by questioning it from the face of the other, from the socio-cultural values, norms and principles that condition it).